2018
DOI: 10.1007/s00213-018-4836-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in trait impulsivity do not bias the response to pharmacological drug challenge in the rat five-choice serial reaction time task

Abstract: RationaleMaladaptive impulsivity is symptomatic of several neuropsychiatric disorders including schizophrenia, attention-deficit hyperactivity disorder (ADHD), and substance abuse disorders; paradigms designed to assess the underlying neurobiology of this behavior are essential for the discovery of novel therapeutic agents. Various models may be used to assess impulsivity as measured by the five-choice serial reaction time task (5-CSRTT), including variable inter-trial interval (ITI) sessions, the selection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
(72 reference statements)
6
7
0
Order By: Relevance
“…Pretreatments with cocaine or MDPV tended to increase measures of impulsivity in HI rats but not consistently and not at significant levels. This finding is similar to what has been reported before in experiments with cocaine 38,39 . Hyatt et al (2019), one of the first papers to describe the effects of MDPV on impulsivity, found that acute administration of MDPV, but not cocaine, led to increases in choice impulsivity in a delay‐discounting task 40 .…”
Section: Discussionsupporting
confidence: 87%
“…Pretreatments with cocaine or MDPV tended to increase measures of impulsivity in HI rats but not consistently and not at significant levels. This finding is similar to what has been reported before in experiments with cocaine 38,39 . Hyatt et al (2019), one of the first papers to describe the effects of MDPV on impulsivity, found that acute administration of MDPV, but not cocaine, led to increases in choice impulsivity in a delay‐discounting task 40 .…”
Section: Discussionsupporting
confidence: 87%
“…≤10%). However, lengthening the ITI from 5 to 10 s produced a dramatic increase in premature responses, a consistent finding that has been widely reported (Robbins, 2002;Blondeau and Dellu-Hagedorn, 2007;Higgins and Silenieks, 2017;Barlow et al, 2018). Accuracy was also reduced at the longer ITI compared to 5-s ITI, although whether this is a consequence of the lower SD (5-s ITI SD=0.75 s; 10-s ITI SD=0.3 s), or longer ITI, or both, is unclear from the present experiments.…”
Section: Characterization Of Performance Across the Five-choice Challsupporting
confidence: 88%
“…Subgrouping rats under the 10-s ITI schedule based on the level of premature responses into "Low" and "High" impulsives (LI vs. HI) highlighted the wide range of responders on this parameter (Dalley et al, 2007;Barlow et al, 2018). Importantly there was a reasonable consistency of performance on this measure over repeated tests.…”
Section: Characterization Of Performance Across the Five-choice Challmentioning
confidence: 90%
“…The principal challenge is to response control, lengthening the ITI from 5 s to 10 s produces a significant increase in both PREM and PSV responses, a consistent and widely reported finding (Robbins, 2002;Jupp et al, 2013;Barlow et al, 2018;Higgins et al, 2020a,b). Subgrouping rats, based on the level of PREM responses under the 10 s ITI schedule, into "Low" and "High" impulsives (LI vs. HI) highlights a wide range of responders typically seen under this schedule (Jupp et al, 2013;Fink et al, 2015;Barlow et al, 2018;Higgins et al, 2020a). Importantly there is a reasonable consistency of performance on this measure over repeated tests as demonstrated by the HI rats having higher PREM scores under the 5 s ITI, albeit at markedly lower levels.…”
Section: Discussionsupporting
confidence: 59%